The effects of mind mapping at while-reading stage on EFL students' reading comprehension at a local high school in Kien Giang - Nguyễn Thị Lan Quỳnh (Trường Đại học Trà Vinh, 2024)
This study aims to explore the effects of mind mapping at while-reading stage on Grade 11 students' reading comprehension and their attitudes towards the effects of mind mapping on their reading ability.